Selective stiffening of fibrin hydrogels with micron resolution via photocrosslinking. (15th March 2019) - Keating, Mark; Lim, Micah; Hu, Qingda; Botvinick, Elliot
Graphical abstract: Abstract: Fibrin hydrogels are used as a model system for studying cell-ECM biophysical interactions. Bulk mechanical stiffness of these hydrogels has been correlated to mechanotransduction and downstream signaling. However, stiffness values proximal to cells can vary by orders of magnitude at the length scale of microns. Patterning of matrix stiffness at this spatial scale can be useful in studying such interactions. Here we present and evaluate a technique to selectively stiffen defined regions within a fibrin hydrogel. Laser scanning illumination activates ruthenium-catalyzed crosslinking of fibrin tyrosine residues, resulting in tunable stiffness changes spanning distances as small as a few microns and a localized compaction of the material. As probed by active microrheology, stiffness increases by as much as 25X, similar to previously observed stiffness changes around single cells in 3D culture. In summary, our method allows for selective modification of fibrin stiffness at the micron scale with the potential to create complex patterns, which could be valuable for the investigation of mechanotransduction in a biologically meaningful way. Statement of Significance: Fibrin hydrogels are used as a naturally derived model to study interactions between cells and their surrounding extracellular matrix (ECM). ECM stiffness influences cell state. Cells in 3D culture considerably modify the stiffness of their pericellular space, which can be quite heterogeneous at the micron-scale. Here we present and evaluate a method to pattern stiffness within fibrin hydrogels using a laser scanning confocal microscope and selective photo crosslinking. We believe that this technique can aid future studies of cell-ECM interactions by enabling researchers to modify the pericellular distribution of stiffness.